2017
DOI: 10.1021/acs.analchem.7b00673
|View full text |Cite
|
Sign up to set email alerts
|

Extended Protein Ions Are Formed by the Chain Ejection Model in Chemical Supercharging Electrospray Ionization

Abstract: Supercharging electrospray ionization can be a powerful tool for increasing charge states in mass spectra and generating unfolded ion structures, yet key details of its mechanism remain unclear. The structures of highly extended protein ions and the mechanism of supercharging were investigated using ion mobility-mass spectrometry. Head-to-tail-linked polyubiquitins (Ubq) were used to determine size and charge state scaling laws for unfolded protein ions formed by supercharging while eliminating amino acid comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(89 citation statements)
references
References 72 publications
5
83
1
Order By: Relevance
“…Numerous studies have found that more highly charged ions are generated by the addition of small organic molecules to the biomolecule solutions undergoing ESI. This process is known as “supercharging.” Some studies suggest that supercharging is the result of denaturation; the organic reagents induce the unfolding of a molecule (ie, conformational change) and changes in droplet surface tension . Other studies suggest that supercharging is due to a direct interaction between biomolecules and supercharging reagents .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have found that more highly charged ions are generated by the addition of small organic molecules to the biomolecule solutions undergoing ESI. This process is known as “supercharging.” Some studies suggest that supercharging is the result of denaturation; the organic reagents induce the unfolding of a molecule (ie, conformational change) and changes in droplet surface tension . Other studies suggest that supercharging is due to a direct interaction between biomolecules and supercharging reagents .…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35][36][37][38][39][40][41][42][43][44][45] Some studies suggest that supercharging is the result of denaturation; the organic reagents induce the unfolding of a molecule (ie, conformational change) and changes in droplet surface tension. [46][47][48][49][50][51] Other studies suggest that supercharging is due to a direct interaction between biomolecules and supercharging reagents. [52][53][54] Loo and coworkers proposed an ESI mechanism to predict and explain how supercharging reagents can increase analyte charge.…”
mentioning
confidence: 99%
“…This leads to protons attaching to the exposed portion of the ion, followed by further extrusion and ultimate ejection of the extended chain (Konermann et al, 2013). Much of the current evidence suggests that folded proteins formed by ESI from buffered aqueous solution ionize by the CRM, small ions by the IEM, and unfolded, disordered proteins by the CEM (Donor et al, 2017). A schematic illustrating these three models of ion formation by ESI is shown in Figure 1.7.…”
Section: Electrospray Ionisationmentioning
confidence: 99%
“…This model of ionisation preserves non-covalent complexes, as it requires less energy, as the ions are not expelled from within the droplet, but the droplet is removed from around them, and is therefore less damaging. It is generally accepted that compact proteins are ionised via the charge residue model (Donor et al, 2017).…”
Section: Esi-ims-ms Instrumentationmentioning
confidence: 99%
“…The unfolded protein chain is partially ejected from the solvent droplet, leading protons to attach to the exposed portion of the ion. The ion is then further extruded from the droplet, gaining more charges, until it is fully ejected from the solvent (Konermann et al, 2013;Donor et al, 2017).…”
Section: Esi-ims-ms Instrumentationmentioning
confidence: 99%